Management education for the nineties - K. B. Hofmeyr (South African Journal of Business Management, 1990)
Management education, and particularly the MBA degree, is facing considerable criticism in the United States and Europe. It is charged with being too analytical in its orientation and out of touch with the needs of the business world. Insufficient attention is paid to areas such as people skills, ethics, and leadership. It is also seen as being out of touch with current trends in business such as the internationalization of business, the trend towards an information/service society, and the renewed interest in organizational culture and participative management. In this article these criticisms are reviewed as well as the major trends taking place overseas and South African management education is evaluated against these themes. The author also reports on research conducted in South Africa to identify what managers perceive to be the most important challenges which will face this country's managers in the nineties. In the light of this research, recommendations are made for making South African management education more relevant. Business school curricula must be contextualized while staying close to international trends. Business schools must also learn from the criticisms being levelled at management education in other parts of the world. They must respond to the demographic trends taking place in South Africa and re-define the role of research in management education.
Keywords: 650